Mortality and Its Risk Factors in Patients with Rapid Eye Movement Sleep Behavior Disorder - Zhou, Junying (Sleep, 2016)
STUDY OBJECTIVES: To determine the mortality and its risk factors in patients with rapid eye movement (REM) sleep behavior disorder (RBD). METHODS: A total of 205 consecutive patients with video-polysomnography confirmed RBD (mean age = 66.4 ± 10.0 y, 78.5% males) were recruited. Medical records and death status were systematically reviewed in the computerized records of the health care system. Standardized mortality ratio (SMR) was used to calculate the risk ratio of mortality in RBD with reference to the general population. RESULTS: Forty-three patients (21.0%) died over a mean follow-up period of 7.1 ± 4.5 y. The SMR was not increased in the overall sample, SMR (95% confidence interval [CI]) = 1.00 (0.73–1.33). However, SMR (95% CI) increased to 1.80 (1.21–2.58) and 1.75 (1.11–2.63) for RBD patients in whom neurodegenerative diseases and dementia, respectively, eventually developed. In the Cox regression model, mortality risk was significantly associated with age (hazard ratio [HR] = 1.05; 95% CI, 1.01–1.10), living alone (HR = 2.04; 95% CI, 1.39–2.99), chronic obstructive pulmonary disease (HR = 3.38; 95% CI, 1.21–9.46), cancer (HR = 10.09; 95% CI, 2.65–38.42), periodic limb movements during sleep (HR = 3.06; 95% CI, 1.50–6.24), and development of neurodegenerative diseases (HR = 2.84; 95% CI, 1.47–5.45) and dementia (HR = 2.66; 95% CI, 1.39–5.08). CONCLUSIONS: Patients with RBD have a higher mortality rate than the general population only if neurodegenerative diseases develop. Several risk factors on clinical and sleep aspects are associated with mortality in RBD patients. Our findings underscore the necessity of timely neuroprotective interventions in the early phase of RBD before the development of neurodegenerative diseases. CITATION: Zhou J, Zhang J, Lam SP, Mok V, Chan A, Li SX, Liu Y, Tang X, Yung WH, Wing YK. Mortality and its risk factors in patients with rapid eye movement sleep behavior disorder. SLEEP 2016;39(8):1543–1550.